Development of E-magazine Based on Flipbook Maker on the Pattern Drafting Home Clothing in the Faculty of Engineering Medan State University - Surniati Chalid; Halida Hanim; Yudhistira Anggraini; Halimul Bahri; Ulfa Annida Damanik (RIRAI Publisher, 2022)
In online learning, lecturers need to modify/develop learning media so that students dont experience difficulties in understanding the learning material. The purpose of this study are: (1) To know how is media development flipbook maker based e-magazine on the pattern drafting of home clothing (2) To know the effectiveness flipbook maker based e-magazine media on the pattern drafting of home clothing. The development model used in this research is the ADDIE. the development procedure (1) Analysis, namely identifying products that are in accordance with the goals of students. (2) Design are, includes designing the initial product and the pattern drafting home clothing. (3) Development, e-magazine media based on Flip book maker will be developed by research hers according to a predetermined design. (4) Implementation (5) Evaluation is carried cut in the form of evaluation formative.